Semantic agent systems foundations and applications - Eloci, Atilla; Kone, Mamadou Tadiou; Orgun, Mehmet A.; SpringerLink (Online service). (Berlin Springer, 2011)
Semantic agent systems are about the integration of the semantic Web, software agents, and multi-agent systems technologies. Like in the past (e.g. biology and informatics yielding bioinformatics) a whole new perspective is emerging with semantic agent systems. In this context, the semantic Web is a Web of semantically linked data which aims to enable man and machine to execute tasks in tandem. Here, software agents in a multi-agent system as delegates of humans are endowed with power to use semantically linked data. This edited book Semantic Agent Systems: Foundations and Applications proposes contributions on a wide range of topics on foundations and applications written by a selection of international experts. It first introduces in an accessible style the nature of semantic agent systems. Then it explores with numerous illustrations new frontiers in software agent technology. Semantic Agent Systems: Foundations and Applications is recommended for scientists, experts, researchers, and learners in the field of artificial intelligence, the semantic Web, software agents, and multi-agent systems technologies.
Part I Introduction to Agents and Semantics -- Part II Engineering Semantic Agent Systems -- Part III Applications of Semantic Agent Systems -- Part IV Future Outlook.
Electronic reproduction.
Keywords: Semantic Web; Multiagent systems; Intelligent agents (Computer software).; Ontologies (Information retrieval).; Electronic books